2004
DOI: 10.1074/jbc.m311493200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inhibiting Vacuolar Acidification on Insulin Signaling in Hepatocytes

Abstract: Previous studies have shown that the endosomal apparatus plays an important role in insulin signaling. Inhibition of endosomal acidification leads to a decrease in insulin-insulin receptor kinase (IRK) dissociation and insulin degradation. Thus, vacuolar pH could function as a modulator of insulin signaling in endosomes. In the present study we show that in primary hepatocytes pretreated with bafilomycin, there is an inhibition of vacuolar acidification. Incubation of these cells with insulin was followed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 48 publications
5
20
0
Order By: Relevance
“…Bafilomycin was previously observed to inhibit insulin-stimulated mitogenesis in primary hepatocytes (44), Swiss 3T3 cells (45), BNL (murine embryonic liver) cells (46), and eight different human cancer cell lines (47). In this study we showed that EGF-stimulated DNA synthesis in primary rat hepatocytes was also inhibited by bafilomycin using both 10 and 100 nM EGF (Fig.…”
Section: Proteomic Analysis Of Rat Liversupporting
confidence: 50%
“…Bafilomycin was previously observed to inhibit insulin-stimulated mitogenesis in primary hepatocytes (44), Swiss 3T3 cells (45), BNL (murine embryonic liver) cells (46), and eight different human cancer cell lines (47). In this study we showed that EGF-stimulated DNA synthesis in primary rat hepatocytes was also inhibited by bafilomycin using both 10 and 100 nM EGF (Fig.…”
Section: Proteomic Analysis Of Rat Liversupporting
confidence: 50%
“…Thus, in our experiments, it is very unlikely that bafilmycin A 1 inhibits the insulin-stimulated 2-DG uptake by perturbing the alkalinizing effect of insulin. Another possibility is that bafilomycin A 1 may inhibit insulin signaling cascades as it did in rat hepatocytes [40]. Then again, Malikova et al [41] demonstrated that bafilomycin A 1 and concanamycin A, another specific inhibitor of VATPase, do not affect insulin signal transduction in adipocytes even though they inhibit insulin-stimulated glucose transport.…”
Section: Discussionmentioning
confidence: 99%
“…These features are particularly important, because acidic pH triggers a conformational change in TeNT and other CNTs, allowing the active subunit to translocate through the endosomal membrane into the cytosol (9,10). Moreover, acidic pH is known to drive the dissociations of ligands, including growth factors, from their receptors and influence their signaling and intracellular targeting (11,12). We sought to address these important questions by preparing chimeras of TeNT H C and ratiometric pHluorin, a pH-sensitive green fluorescent protein mutant (13).…”
mentioning
confidence: 99%